Creativity: challenges to a key concept for the XXI century - Morais, Maria de Fátima (2013)
Research about creativity in the field of psychology has come a long way. However, some persistent challenges remain about this concept and it is difficult to implement good practices from ambiguous or unclear conceptions. After introducing the concept of creativity as a confluence of cognitive, emotional and social requirements, we will share three topics of discussion - theoretical controversy with pragmatic implications; common conceptual misunderstandings (myths) damaging the investment on creativity; and potentialities and risks intrinsic to the assessment domain. These challenges aim to encourage readers to question and to invest in a crucial psychological and social requirement for the twenty-first century: creative skills for solving problems.